Granulomatosis With Polyangiitis in a Patient on Programmed Death-1 Inhibitor for Advanced Non-small-cell Lung Cancer - Sibille, Anne; Alfieri, Romain; Malaise, Olivier; Detrembleur, Nancy; Pirotte, Michelle; Louis, Renaud; Duysinx, Bernard (Frontiers in Oncology, 2019)
Objectives: To contribute to a precise and thorough knowledge of immune-related adverse events (irAE) induced by immune checkpoint inhibitors (ICI) and to emphasize the importance of this specific form of toxicity in terms of potential predictive value and long-term effects. Materials and Methods: We report the first case of granulomatosis with polyangiitis (GPA) in a patient treated with an anti-Programmed Death protein-1 (PD-1) antibody for advanced non-small-cell lung cancer (NSCLC). Results: After a single dose of this drug the patient showed severe myositis associated with a high anti-PR3 anti-neutrophil cytoplasmic antibody titer. Discontinuation of the anti-PD-1 and introduction of corticoids led to a remission of the irAE. Regarding tumor a partial response was noted. A year later a neutrophilic, sterile pleural exudate and cutaneous lesions appeared with the pathological findings of neutrophilic vasculitis. Retreatment with corticoids induced a new remission of symptoms. It remains unclear whether GPA was preexisting and clinically silent but revealed by the use of ICI or primarily induced by this treatment. Conclusions: irAE are rare when anti-PD-1 antibodies are used in monotherapy. They present with a distinct clinical picture and temporal course and require specific treatment. Patients with irAE usually have a favorable oncological outcome.